Upaya Meningkatkan Keterampilan Permainan Bola Voli Menggunakan Alat Bantu Pembelajaran di Kelas X SMKN 2 Surakarta - Yoga Yudha Perwira; Yantri Ayu Nur Widayat; Dony Alif Utomo; Dandi Mahitsa; Manshuralhudlori Manshuralhudlori; Andi Mustofa; Mariyanto Mariyanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims at exploring the enhancement of volleyball playing skills with the use of learning aids which is conducted in SMKN 2 Surakarta. This study employs Classroom Action Research (CAR) within 2 cycles which comprise of 4 stages for each cycle. The stages are planning, Action (Implementation), observation, and reflection. This study involves 36 students from tenth grade of PPLG A of SMKN 2 Surakarta, consisting of 28 male and 8 female learners. The data sources in this study came from the students, the researcher, and the teacher playing a role as a collaborator. Data collection techniques included a test and an observation. Data validity was ensured using data triangulation techniques. Data analysis employed qualitative descriptive techniques based on percentage qualitative analysis. The analysis results indicated that there is an enhancement in volleyball playing skills in the first cycle, with a completion rate of 58.3%, or 21 out of 36 students. The enhancement continued in the second cycle, with a completion rate of 86.1%, or 31 students meeting the proficiency criteria with a minimum mastery level of 75, while 5 students did not meet the criteria. Based on the results, it is concluded that the use of learning aids can significantly enhance volleyball playing skills in the tenth-grade learners of PPLG A at SMKN 2 Surakarta